Preparation and Characterization of Biodegradable Films From Sago Starch and Poly(Vinyl Alcohol) Blends - Widiarto, Sonny (2004)
Biodegradable films of sago starch and poly(vinyl alcohol) (PVA) blends (SP) have been prepared by solution casting method. Glycerol was used as a plasticizer. Sodium borate (borax) and glutaraldehyde were used to increase the compatibility of sago starch and PVA. The optimum amount of glycerol is 20% (w/w). The optimum values of tensile strength and elongation at break of the films are obtained with an addition of 8% (w/w) sodium borate (borax) or 62.5% (w/w) glutaraldehyde. Both pure PVA and sago starch films are apparently transparent. However, their blend films are slightly opaque probably due to phase separation. Increase the amount of PVA in the film leads to an increase of the tensile strength and reduces the elongation of films. Both borax and glutaraldehyde increase the elongation at break of the sago starch – PVA blend films, but improvement of tensile strength is only obtained when the films are added with borax. The films produced were characterized by FTIR spectroscopy, differential scanning calorimetry (DSC), thermogravimetry analysis (TGA), X-ray diffraction (XRD), and scanning electron microscopy (SEM). FTIR spectrum of sago starch – PVA – borax (SPB) film showed the shifting of characteristic O-H stretching vibration peak to a higher wavelength number at 3426 cm-1 and an increase of O-H bending intensity of absorbed water peak at 1638 cm-1, indicating more tightly bound water present in the film in comparison with that of SP film. SEM studies show that SPB film was porous. Meanwhile, TGA studies revealed that decomposition of SPB film is a three-stage process. XRD studies indicated that the degree of crystallinity of SPB film is higher than that of SP film. FTIR spectrum of sago starch – PVA – glutaraldehyde (SPG) film shows the appearance of aldehyde’s carbonyl group at 1717 cm-1. This peak should be disappeared after the acetalation reaction. However, the peak is weaker than that of normal aldehyde, indicating the occurrence of incomplete acetalation reaction. SPG film has a more compact structure than that of SP film as shown by SEM. Thermal decomposition of SPG film is also in a three-stage process. XRD studies indicated that the degree of crystallinity of SPG film is lower than that in SP film. Tensile strength of both SPB and SPG films increase after storage treatment, whereas their elongation decrease. The changes of tensile properties could be related to both the changes on crystallinity and the loss of plasticizer during storage. The B-type crystallinity appeared on the SPB samples after two months of storage, but the same crystallinity was not observed in SPG samples. Biodegradation of original and modified sago starch – PVA blend films have been studied by soil burial method. Percentage of weight loss of both SPB and SPG films increase with an increase of sago starch content.